Diatoms as indicators of hydrological and climatic changes in Laguna Potrok Aike (Patagonia) since the Late Pleistocene - Recasens, Cristina; Ariztegui, Daniel; Maidana, Nora Irene; Zolitschka, Bernd; PASADO Science Team (Palaeogeography, Palaeoclimatology, Palaeoecology)
Southern South America is a key site to study climate variability in the Southern Hemisphere, allowing for a wide variety of climatic archives. Recently, several investigations using lacustrine sediments have provided an enormous amount of information to reconstruct past environmental changes. In the framework of the Potrok Aike Maar Lake Sediment Archive Drilling Project (PASADO) more than 500. m of sediment cores were retrieved from the center of this lake.This contribution is centered in the diatom record of a core covering over the last 50. cal. ka BP. Nine statistically significant zones were determined based on changes in the assemblages of more than 200 species of diatoms, showing changes in productivity throughout time. Although it appears that the presence of mass waste events may have triggered some peaks in productivity, large fluctuations in diatom abundance and changes in species assemblages coincide with distinctive Antarctic warm events, A2 and A1, described for Antarctic ice cores at around 44.5 and 38.5 kyr BP respectively (Blunier and Brook, 2001). Furthermore, a smaller diatom peak may account for the A3 event compatible with a new OSL-based chronological model. Up to now they have only been described for Antarctica, but the fact that these events are recorded in southern Patagonia indicates their magnitude and importance for climate in the Southern Hemisphere. Fil: Recasens, Cristina. Universidad de Ginebra. Facultad de Ciencias. Sección de Ciencias de la Tierra; Suiza Fil: Ariztegui, Daniel. Universidad de Ginebra. Facultad de Ciencias. Sección de Ciencias de la Tierra; Suiza Fil: Maidana, Nora Irene. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Biodiversidad y Biología Experimental; Argentina Fil: Zolitschka, Bernd. Universitat Bremen. Institut Fuer Geographie; Alemania Fil: PASADO Science Team. Universidad de Ginebra. Facultad de Ciencias. Sección de Ciencias de la Tierra; Suiza